[Ulotka w obronie więźniów politycznych z KOR] . Leaflet in defense of political prisoners from KOR - Służba Informacyjna. (Służba Informacyjna, 1984)
B&w print on white paper. Flier, issued in defense of Adam Michnik, Jacek Kuroń, Zbigniew Romaszewski and Henryk Wujec, former members of the Workers' Defense Committee, informs about their trial, presents their profiles with photos, and calls for solidarity with the dissidents.